The Importance of Alaska for Climate Stabilization, Resilience, and Biodiversity Conservation - Vynne, Carly; Dovichin, Erin; Fresco, Nancy; Dawson, Natalie; Joshi, Anup; Law, Beverly E.; Lertzman, Ken; Rupp, Scott; Schmiegelow, Fiona; Trammell, E. Jamie (Frontiers in Forests and Global Change, 2021)
Alaska is globally significant for its large tracts of intact habitats, which support complete wildlife assemblages and many of the world’s healthiest wild fisheries, while also storing significant amounts of carbon. Alaska has 1/3 of U.S. federal lands, the bulk of the U.S.’s intact and wild lands, and an estimated 62 percent of the country’s total terrestrial ecosystem carbon on federal lands. Managing Alaska’s public lands for climate and biodiversity conservation purposes over the next 30-50 years would provide meaningful and irreplaceable climate benefits for the U.S. and globe. Doing so via a co-management approach with Alaska’s 229 federally recognized tribes is likely not only to be more effective but also more socially just. This paper lays out the scientific case for managing Alaska’s public lands for climate stabilization and resilience and addresses three primary questions: Why is Alaska globally meaningful for biodiversity and climate stabilization? Why should Alaska be considered as a key element of a climate stabilization and biodiversity conservation strategy for the U.S? What do we need to know to better understand the role of Alaska given future scenarios? We summarize evidence for the role Alaska’s lands play in climate stabilization, as well as what is known about the role of land management in influencing carbon storage and sequestration. Finally, we summarize priority research that is needed to improve understanding of how policy and management prescriptions are likely to influence the role Alaska plays in global climate stabilization and adaptation.